Globalisering, modernisme en postmodernisme: In stede van die liefde (2005) van Etienne van Heerden - Visagie, Andries (Tydskrif vir Letterkunde, 2010)
In the 1990s postmodernism as a literary phenomenon led to the development of a lively literary discourse in Afrikaans. However, in contemporary narrative criticism postmodernism rarely features as a theoretical framework for studies of new Afrikaans writing. In poetry criticism postmodernism still enjoys some currency, whereas some critics hold the position that there should be stronger acknowledgement of modernist elements in the development of Afrikaans poetry. In an effort to grasp the manifestation of postmodernism in contemporary Afrikaans prose, this article focuses on globalisation and modernism as two unique challenges to thinking about postmodernism that prevail in Etienne van Heerden’s novel In stede van die liefde (In Cities of Love, 2005). The article identifies three problems in theoretical reflections about postmodernism, namely a too narrowly conceived view of postmodernism, a lack of recognition of the continuities between modernism and postmodernism, and the resulting neglect of modernism. Furthermore, the article offers a critical interrogation of globalisation in its guise as a new master narrative in the light of recent developments in the postmodern era. Through a reading of Van Heerden’s novel, the interrogation focuses on the motifs of slippage and substitution in In stede van die liefde. The representation of space in the novel includes both the urban and the rural and points to ‘glocalisation’, a term that refers to the interconnection between the local and the global. The author proposes that globalisation in the guise of a diffuse and multidimensional master narrative, produces a yearning for older master narratives leading to the reaffirmed presence of modernist elements in a manifestly postmodernist novel such as In stede van die liefde. The challenge is to acknowledge modernist elements in contemporary literature using a theoretical approach that exhaustively accounts for the link between postmodernism and globalisation – new manifestations of modernism can no longer be examined with outdated theories about modernist literature.